Physical Medicine and Rehabilitation Program Directors' Perspectives on US Medical Licensing Examination Step 1 Scoring Changes. (December 2021) - Chator, Areeb A.; Ganesh Kumar, Nishant; Drolet, Brian C.; Sullivan, William J.; Kennedy, David J.
Abstract : Abstract: In response to increasing dependence on US Medical Licensing Examination Step 1 scores for resident selection, and to improve medical student well-being and education, the Federation of State Medical Boards and the National Board of Medical Examiners announced that no sooner than 2022, Step 1 score reporting would change from numeric to pass/fail. To gauge the impact that this change will have on the residency application process in physical medicine and rehabilitation, an anonymous survey was electronically distributed to program directors of all accredited physical medicine and rehabilitation residency programs in the United States. A response rate of 49% was obtained. In total, 13% of program directors agreed that the scoring change was a good idea. Eighty percent of program directors felt that the change would increase emphasis on Step 2 clinical knowledge in the application process and that it will be more difficult to objectively compare applicants. Among free-text responses to the survey, 70% disapproved, 10% approved, and the remaining 20% were neutral to the change. The results of this survey show that many physical medicine and rehabilitation program directors are concerned about the implications of the Step 1 score reporting change. These data can serve as a helpful guide to program directors and students preparing for a pass/fail Step 1. Abstract : Supplemental digital content is available in the text.